A Retrospective Study of Management of Congenital Hydronephrosis, is Early Detection Necessary? - Shah, R; Hamal, B K; Bhandari, B B (Medical Journal of Shree Birendra Hospital, 2006)
A Retrospective Study of Management of Congenital Hydronephrosis, is Early Detection Necessary?